2019
DOI: 10.1016/j.rbo.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Perfil dos pacientes diagnosticados com displasia do desenvolvimento do quadril

Abstract: Objective  To describe the profile of patients with developmental dysplasia of the hip (DDH) diagnosed by physical and ultrasound examination, with the implementation of a protocol for the treatment and follow-up of DDH. Methods  A cross-sectional study with DDH patients born between January 2014 and December 2016, in the city of Pelotas, Southern Brazil. Ethnicity, gender, birth weight, fetal presentation, affected side of the hip, gestational age, maternal age and family history were considered. The data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
(125 reference statements)
0
5
0
2
Order By: Relevance
“…Barbosa and Albernaz 8 were the only authors who tried to estimate the prevalence of DDH in Brazil, in a retrospective study performed in the School of Medicine at Universidade Católica de Pelotas. The authors reported many potential selection biases because the analysis was performed with a small number of cases identified through the patients' medical records.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barbosa and Albernaz 8 were the only authors who tried to estimate the prevalence of DDH in Brazil, in a retrospective study performed in the School of Medicine at Universidade Católica de Pelotas. The authors reported many potential selection biases because the analysis was performed with a small number of cases identified through the patients' medical records.…”
Section: Discussionmentioning
confidence: 99%
“…Barbosa e Albernaz 8 foram os únicos autores que tentaram estimar a prevalência de DDQ no Brasil, em estudo retrospectivo realizado na Faculdade de Medicina da Universidade Católica de Pelotas. Os autores relataram muitos potenciais vieses de seleção, porque a análise foi realizada em um pequeno número de casos identificados a partir dos prontuários dos pacientes.…”
Section: Discussionunclassified
“…In the United States, the Pediatric Orthopedic Society of North America (POSNA) recommends that a physical examination be carried out during the first months of life primarily by a pediatrician, and when positive, referral for a more detailed analysis with a pediatric orthopedist to confirm or reject the diagnosis. USG is performed for positive cases and those at high risk for DDH, with an agreement of 87.5% between the echogram and the positive result of the physical examination 12,13 . The newborn healthcare guide for orthopedic problems from the Ministry of Health (MoH) in Brazil recommends the Ortolani maneuver in the first two days of life and in subsequent consultations 14,15 .…”
Section: Discussionmentioning
confidence: 98%
“…It is also important to mention femoral nerve palsy. These complications present a good resolvability when there is suspension of the established treatment (BARBOSA;Albernaz, 2019).…”
Section: Pavlik Suspendermentioning
confidence: 99%